Bibliometric Analysis of the Development of Innovative Entrepreneurship Literature Based on Sustainability Principles - Loso Judijanto; Ardi Azhar Nampira; Asmirin Noor (West Science Journal Economic and Entrepreneurship, 2025)
This study presents a bibliometric analysis of the scholarly literature on innovative entrepreneurship with a specific focus on its integration with sustainability principles. Using data from the Scopus database covering publications from 2001 to 2025, the analysis employed VOSviewer to visualize co-authorship networks, citation patterns, and keyword co-occurrence maps. The results reveal a dynamic and interdisciplinary field shaped by influential contributors such as Audretsch, Acs, and Thurik, with collaborative hubs concentrated in the United States and Europe. The conceptual core of the literature revolves around economic development, innovation activity, and entrepreneurial behavior, while recent trends point to a growing emphasis on sustainability, education, and digital transformation. Overlay and heatmap visualizations demonstrate an evolving research agenda increasingly aligned with global sustainability goals. The study identifies gaps in geographical representation and calls for further exploration of impact-driven entrepreneurship, particularly in emerging economies. These findings offer valuable insights for scholars, policymakers, and practitioners aiming to advance sustainable innovation through entrepreneurship.